2022
DOI: 10.3390/atmos13030419
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Variability of Wind Erosion Climatic Erosivity and Their Relationships with Large-Scale Atmospheric Circulation in Xinjiang, China

Abstract: Xinjiang has a serious wind erosion problem due to its fragile ecological condition and sensitivity to climate change. Wind erosion climatic erosivity is a measure of climatic factors influencing wind erosion; evaluating its spatiotemporal variations and relationship with the large-scale circulation pattern can contribute to the understanding of the climate change effect on wind erosion risk. Thus, this study quantified the wind erosion climatic erosivity and examined the connections between climatic erosivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Relevant research shows a high correlation between regional meteorological elements and the factor index of wind erosion erosivity. In the study on the influence of climate conditions on the wind erosion erosivity in Xinjiang (Wang et al, 2022b), it is found that the meteorological elements that influence the C value are wind speed, temperature, precipitation amount, and relative humidity in descending order of influence degree. In terms of geographical distribution, the elements of precipitation amount and relative humidity significantly influence northern Xinjiang.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research shows a high correlation between regional meteorological elements and the factor index of wind erosion erosivity. In the study on the influence of climate conditions on the wind erosion erosivity in Xinjiang (Wang et al, 2022b), it is found that the meteorological elements that influence the C value are wind speed, temperature, precipitation amount, and relative humidity in descending order of influence degree. In terms of geographical distribution, the elements of precipitation amount and relative humidity significantly influence northern Xinjiang.…”
Section: Discussionmentioning
confidence: 99%